Learning effectiveness of simulation based teaching in Gynaecology and Obstetrics among medical students: a mixed-methods study - Mohsin, Shamaila; Jamil, Brekhna; Khan, Kiran Imtiaz; Virk, Safiullah; Ahmad, Abdul Momin Rizwan (Frontiers in Medicine, 2025)
IntroductionSimulation-Based Teaching (SBT) has emerged as an educational strategy to enhance clinical competence among medical students, particularly in Gynaecology and Obstetrics.ObjectiveThis study assessed the effectiveness of learning SBT and explored the enablers and challenges associated with implementing SBT in Gynaecology and Obstetrics.MethodsUsing a sequential explanatory mixed methods approach a study was conducted in Skills Lab at Pakistan Emirates Military Hospital (PEMH), Rawalpindi during May–Sep 2024. A pre/post design study was conducted on final-year medical students using a validated questionnaire Simulation Learning Effectiveness Inventory (SLEI-SCM). The qualitative component explored students’ and faculty perception of SBT through In-depth interviews. The quantitative data was analyzed using SPSS (V.25) while the qualitative data was conducted through Braun and Clarke Thematic framework.ResultsA total of 190 participants participated in the quantitative study. The pre-training mean score of the participants 89.4 significantly improved to 139.5 post-training (Mean Difference = 50.1). Post-intervention results revealed significant improvements (p < 0.001) in learning effectiveness such as workshop content and resource availability. The in-depth interviews conducted with 23 participants, students and facilitators, revealed several key themes.ConclusionSBT significantly enhanced undergraduate learning outcomes in Gynecology and Obstetrics, in workshop content, resource availability, and clinical confidence.